Revalidation and redescription of a gobionine species Microphysogobio bicolor (Nichols, 1930) (Teleostei: Cypriniformes) from the Yangtze River Basin, China - Sun, Zhixian; Zhao, Yahui (Zootaxa, 2022)
Microphysogobio bicolor (Nichols, 1930), a species which has long been synonymized with Microphysogobio fukiensis (Nichols, 1926), is revalidated in this study, based on morphological comparison and molecular phylogenetic analysis. The species can be distinguished from congeners by the following characters: mouth horseshoe-shaped, central portion of anterior papillae arranged in one row, tightly contact with each other, equal or slightly larger than all other papillae on upper lip; lateral-line scales 36–38; branched anal-fin rays 5; posterior chamber of air-bladder length equal to eye diameter; vertebrae 4+32; body usually sharply bicolored. The significant Cyt b gene sequence divergence between M. bicolor and its congeners also strongly support that it is a valid species which represents an individual clade sister to the M. luhensis–M. kachekensis–M. yunnanensis clade. A redescription of M. bicolor and a diagnostic key to all valid Microphysogobio in the Yangtze River Basin are also provided in this study.